CONSUMER PERCEPTION OF LISTRIK PINTAR PT. PLN (PERSERO) IN MANADO AND TOMOHON - Tamauka, Virginia (Universitas Sam Ratulangi, 2014)
The Listrik Pintar is a new innovation from PLN that to easier, freedom, and comfortable for the customer that using this new service. Listrik Pintar is a sollution that helpful the customer to using electricity more saving and disciplinary. Where in usage this new service the filling and systematization electricity do by itself. The research objective of this research is to analyze the customer perception of Listrik Pintar in Manado and Tomohon. Theory related research are consumer behavior and consumer perception. The population is the customer that already using Listrik Pintar and there are 10 informants that every informants have different perceptions about Listrik Pintar, and also the informants have different background so the perceptions very variation. Researcher used qualitative methods to explain the result of research. Result and conclusion is there are several categorization customer opinion that makes the customer choose and select to using this new service, such as Value, Lifestyle, and Decision Making. So that, before buy or using product or service the usage must to looking out or seek the product or service. Keywords: consumer perception, new service